Cats - Hamer, Martyn; Forsey, Christopher (London ; New York : F. Watts, 1983)
An introduction to different kinds of cats and their characteristics.
Includes index.
3.8
3-6
Keywords: Cats -- Juvenile literature; Cats; Cats; Cats